2021
DOI: 10.2147/rmhp.s294731
|View full text |Cite
|
Sign up to set email alerts
|

Study to Alter the Nuisance Effect of Non-Response Using Scrambled Mechanism

Abstract: Introduction In biometric sample surveys, our objective is to get ready-made information for future planning and policy implementations related to the subject matters of highly sensitive issues. In such situations, we apply randomized response/scrambled response techniques. There are many highly sensitive issues which need to be examined over time as they may have a tendency to change. To get rid of these types of practical cases we need a scrambled response technique on successive occasions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recently, Singh et al [ 25 ] developed two new quantitative randomized response models which were shown to be better than the existing models in terms of efficiency as well as privacy protection level. In another study, Singh et al [ 26 ] utilized Poisson distribution to develop a three-stage randomized response model which helps in estimating the mean number of persons having a sensitive attribute.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Singh et al [ 25 ] developed two new quantitative randomized response models which were shown to be better than the existing models in terms of efficiency as well as privacy protection level. In another study, Singh et al [ 26 ] utilized Poisson distribution to develop a three-stage randomized response model which helps in estimating the mean number of persons having a sensitive attribute.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [13] studied elimination of the influence of non-response using the randomized scrambling technique. Gupta et al [14] developed an estimator of the population variance using the Diana and Perri [7] randomization strategy.…”
Section: Introductionmentioning
confidence: 99%